Islamism without commotion: the religious transformation of Tuak Kampong in West Lombok - Pajar Hatma Indra Jaya; S Saptoni; Muhammad Izzul Haq (Indonesian Journal of Islam and Muslim Societies, 2023)
The Islamic revival movement is often considered a threat to other religious groups. Many studies on the issues have presented the dark sides of religion, wherein Islamic movements often turned into political ones leading to religion-based fundamentalism, violence, and terrorism. The current research explicates the process and characteristics of Islamism in a democratic climate by investigating a case of religious transformation in a traditional kampong formerly known for producing tuak in West Lombok. The Islamic movement, or to be precise, purification, is recently quite prevalent in the area. It relates to the early history of Islamization in Lombok, which pitted Islam against Hinduism and other local traditions. Such confluences generated rules and regional Islamic variants that are often considered heretic. Qualitative data for this study was gathered through observations, desk study, and interviews. This research found that the Islamization process observed in the tuak kampong displays unique characteristics different from those that commonly portray Islamic movements. Islamization in West Lombok was carried out without any commotion due to its non-coercive, outward-looking, and rational factors. These attributes are apparent in the three processes of transformation, the first is non-coercive cultural transformation through education and awareness, the second refers to structural change achieved through legal arrangement, and the third is rational transformation through community empowerment programs.